Application of perovskite quantum dot material to optical composite membrane material

Perovskite quantum dots are encapsulated by halide matrix passivation and solid-state inorganic materials, and luminescent masterbatches are prepared in combination with polymer substrates, which solves the problems of poor stability and optical performance optimization in optical composite film applications, and achieves an optical composite film with high stability and excellent optical performance.

CN119910934AInactive Publication Date: 2025-05-02SHENZHEN TIANNUOTONG OPTOELECTRONICS TECH

Patent Information

Application Number
CN202510405448.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-02
Publication Date
2025-05-02
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Perovskite quantum dot materials have poor stability and optical performance optimization problems in optical composite film applications, mainly due to their surface defects and sensitivity to external water and oxygen.

Method used

The surface of perovskite quantum dots is passivated by a halide matrix, and encapsulated with solid inorganic materials such as silicon dioxide, silicon nitride and alumina to isolate external water and oxygen, combine with polymer substrates to prepare luminescent masterbatches through melt blending, and then prepare light diffusion plates and functional films through coextrusion, and finally assemble into an optical composite film material through a hot pressing process.

Benefits of technology

It significantly improves the environmental stability and optical performance of perovskite quantum dots, extends service life, improves the weather resistance and stability of optical composite film materials, and meets the optical performance requirements of different application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119910934A_ABST
    Figure CN119910934A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of perovskite quantum application, and discloses application of a perovskite quantum dot material to an optical composite film material, which comprises the following steps: S1, quantum dot packaging: firstly passivating the surface of a perovskite quantum dot by using a halide matrix, and then isolating perovskite from external water and oxygen by using a solid inorganic material to obtain a perovskite quantum dot material; s2, preparing a luminescent master batch: carrying out melt blending on the perovskite quantum dot material and a polymer base material to prepare the luminescent master batch; s3, extruding the light diffusion plate; s4, pretreating the membrane material; s5, preparing a functional film; and S6, assembling the optical composite membrane material. The surface of the perovskite quantum dot is passivated through the halide matrix, the solid inorganic material is used for packaging, the environmental stability and the optical performance of the quantum dot are remarkably improved, the halide matrix repairs surface defects and improves the quantum yield, the solid inorganic material isolates water and oxygen, and the service life is prolonged; therefore, the weather resistance and the stability of the subsequent optical composite film material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of perovskite quantum application, and in particular to the application of perovskite quantum dot material to optical composite film material. Background Art

[0002] With the rapid development of modern optical technology, optical composite films are increasingly used in many fields such as display, lighting, optoelectronic devices, etc., and the requirements for their performance are becoming increasingly stringent. Perovskite quantum dots, as a material with unique optical properties, have shown great potential in improving the performance of optical composite films. However, to give full play to their advantages, the key lies in solving the problems of their stability and optical performance optimization.

[0003] Traditional perovskite quantum dots have many defects on their surfaces, which results in low quantum yield and limited luminous efficiency. In addition, perovskite quantum dots are easily affected by external water and oxygen and have poor stability in the environment, which leads to reduced weather resistance of perovskite quantum dots during application and processing in optical composite film materials, thereby affecting the stability of optical composite film materials. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present invention provides an application of a perovskite quantum dot material to an optical composite film material, which solves the problem that the perovskite quantum dots are easily affected by external water and oxygen, have poor stability in the environment, and affect the performance of the optical composite film material.

[0005] To achieve the above objectives, the present invention is implemented by the following technical solution: A perovskite quantum dot material is applied to an optical composite film material, comprising the following steps: S1. Quantum dot encapsulation: First, the surface of the perovskite quantum dots is passivated with a halide matrix, and then the perovskite is isolated from the external water and oxygen with a solid inorganic material to obtain the perovskite quantum dot material; S2, preparing luminescent masterbatch: preparing luminescent masterbatch by melt blending perovskite quantum dot material and polymer substrate; S3, light diffusion plate extrusion: preparing a light diffusion plate by co-extrusion of luminescent masterbatch, light diffusion substrate and titanium dioxide, wherein the luminescent masterbatch is uniformly dispersed in the light diffusion substrate; S4, film material pretreatment: cleaning and activation of the light diffuser surface; S5. Functional film preparation: co-extruding the functional film material and the perovskite quantum dot material to prepare a functional film containing the perovskite quantum dot material; S6. Assembling optical composite film materials: The treated light diffusion plate and the functional film are assembled into optical composite film materials through a hot pressing process.

[0006] Preferably, the solid inorganic material in S1 includes silicon dioxide, silicon nitride and aluminum oxide.

[0007] Preferably, the polymer substrate in S2 includes polyethylene, polypropylene, and polyethylene terephthalate. The polymer substrate is formed into a porous structure through a resin base material foaming technology, and perovskite quantum dots are introduced to prepare perovskite luminescent masterbatch through a single screw extruder.

[0008] Preferably, the concentration of the perovskite quantum dot material added in S2 is 1% to 10% of the weight of the luminescent masterbatch.

[0009] Preferably, the light diffusion substrate in S3 comprises polymethyl methacrylate, polycarbonate and cycloolefin copolymer, and the weight ratio of the luminescent masterbatch to the light diffusion substrate is 1:99 to 20:80.

[0010] Preferably, the S4 specifically comprises the following steps: S101, placing the light diffusion plate into an ultrasonic cleaning machine for cleaning to remove tiny particles and impurities; S102, placing the cleaned light diffuser plate into a plasma treatment device to cause a chemical reaction on the surface of the light diffuser plate to form active sites; S103, coating a layer of tackifier on the surface of the light diffuser plate.

[0011] Preferably, the functional film in S5 comprises an anti-reflection film, an anti-scratch film and a brightness enhancement film, and the thickness of the functional film is 0.1 μm-10 μm.

[0012] Preferably, in S6, the light diffuser plate and the functional film are integrated into a multifunctional film layer by a heat press.

[0013] The present invention provides an application of perovskite quantum dot material to optical composite film material. It has the following beneficial effects: 1. The present invention passivates the surface of perovskite quantum dots by a halide matrix and encapsulates them with solid inorganic materials, thereby significantly improving the environmental stability and optical properties of the quantum dots. The halide matrix repairs surface defects and improves quantum yield, and the solid inorganic material isolates water and oxygen to extend the service life, thereby improving the weather resistance and stability of subsequent optical composite film materials.

[0014] 2. In the present invention, perovskite quantum dots are combined with functional films so that the perovskite is located in the outermost layer for surface modification and functionalization. Specific chemical groups or functional molecules can be modified on the surface of quantum dots to better meet the requirements of optical performance of optical composite films in different application scenarios, meet the needs of different application scenarios, and increase the practicality and applicability of optical devices.

[0015] 3. In the present invention, the polymer substrate is foamed by the resin base material to form a porous structure, which provides a uniformly dispersed carrier for the perovskite quantum dots, enhances the binding force between the quantum dots and the substrate, and introduces the quantum dots into the porous structure through a single screw extruder to prepare the perovskite luminescent masterbatch, thereby achieving efficient dispersion and stable encapsulation of the quantum dots, improving the luminescence uniformity and stability of the luminescent masterbatch, simplifying the preparation process, reducing costs, and ensuring the optical properties of the optical composite film material. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 The present invention is a flow chart of the application of a perovskite quantum dot material to an optical composite film material. DETAILED DESCRIPTION

[0017] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0018] Please refer to the attached Figure 1 The embodiment of the present invention provides an application of a perovskite quantum dot material to an optical composite film material, comprising the following steps: S1. Quantum dot encapsulation: First, the surface of the perovskite quantum dots is passivated with a halide matrix, and then the perovskite is isolated from the external water and oxygen with a solid inorganic material to obtain the perovskite quantum dot material; S2, preparing luminescent masterbatch: preparing luminescent masterbatch by melt blending perovskite quantum dot material and polymer substrate; S3, light diffusion plate extrusion: preparing a light diffusion plate by co-extrusion of luminescent masterbatch, light diffusion substrate and titanium dioxide, wherein the luminescent masterbatch is uniformly dispersed in the light diffusion substrate; S4, film material pretreatment: cleaning and activation of the light diffuser surface; S5. Functional film preparation: co-extruding the functional film material and the perovskite quantum dot material to prepare a functional film containing the perovskite quantum dot material; S6. Assembling optical composite film materials: The treated light diffusion plate and the functional film are assembled into optical composite film materials through a hot pressing process.

[0019] Specifically, in S1, the surface of the perovskite quantum dots is passivated by a halide matrix and encapsulated with a solid inorganic material, which significantly improves the environmental stability and optical properties of the quantum dots. The halide matrix repairs surface defects and improves the quantum yield. The solid inorganic material isolates water and oxygen, prolongs the service life, and there is no need to use a water and oxygen barrier layer. In addition, the quantum dots encapsulated by the highly stable solid inorganic package still maintain stable luminescence in a high temperature and high humidity environment, thereby improving optical weather resistance. In S2, the encapsulated perovskite quantum dots and the polymer substrate are melt-blended to prepare a luminescent masterbatch, so as to achieve uniform dispersion of the quantum dots and form a stable composite system, thereby simplifying the process and reducing costs. The luminescent masterbatch has high luminous efficiency and tunable emission wavelength, which ensures that when preparing the light diffuser plate, the quantum dots can be evenly distributed in the light diffuser substrate, providing the light diffuser plate with stable luminous performance and achieving effective regulation and conversion of light. In S3, the luminescent masterbatch, the light diffusion substrate and titanium dioxide are co-extruded to prepare a light diffusion plate, so that the luminescent masterbatch is evenly dispersed in the light diffusion substrate. The light diffusion plate can achieve uniform diffusion of light and improve the utilization efficiency of light. At the same time, the addition of titanium dioxide can further enhance the scattering effect of light, so that the subsequent preparation of optical composite film materials has better application performance in the fields of lighting and display, and improves the visual effect of the product; In S4, the surface of the light diffuser plate is cleaned and activated, which can improve the bonding force and interface compatibility between the subsequent light diffuser plate and the functional film layer. The surface of the pre-treated light diffuser plate is clean and activated, and is tightly bonded to the functional film layer to avoid delamination or peeling. At the same time, the activation treatment generates active groups such as free radicals and unsaturated bonds on the surface of the light diffuser plate, increases the surface energy, and significantly improves the bonding force between the light diffuser plate and the functional film, ensuring that when assembling the optical composite film material, the layers can be tightly bonded, thereby improving the overall stability and performance of the film material. In S5, the functional film material and the perovskite quantum dots are co-extruded to prepare a functional film containing quantum dots. The addition of the perovskite quantum dot material can further enhance the optical properties of the functional film, so that it can better meet the requirements of different application scenarios for optical properties and meet the needs of different application scenarios. At the same time, the quantum dots can be in the outermost layer, directly absorbing the excitation light and converting it into a specific wavelength of light for emission, which can significantly improve the color gamut and color purity of the display, making the image color more vivid, rich and realistic, and improving the display quality; S6 assembles the processed light diffuser plate and functional film into optical composite film material through hot pressing process to achieve the integration and optimization of multi-layer structure. The hot pressing process ensures the close combination of each layer and the strong bonding between each layer, while ensuring the stability of the optical and mechanical properties of the optical composite film material, so that it can meet various needs in practical applications. The optical composite film material has high light transmittance, high color gamut and high brightness, and is suitable for high-end display, lighting applications or backlight modules, etc.

[0020] The solid inorganic materials in S1 include silicon dioxide, silicon nitride and aluminum oxide.

[0021] Specifically, solid-state inorganic materials are used to encapsulate perovskite quantum dots to form a dense protective layer, isolating them from external water and oxygen erosion, significantly improving the environmental stability of quantum dots. At the same time, these solid-state inorganic materials have high chemical inertness and excellent barrier properties, which can effectively prevent quantum dots from degrading in high humidity and high temperature environments, while maintaining their high quantum yield and luminous efficiency, extending their service life. At the same time, their good optical transparency ensures that they will not excessively affect the luminescence characteristics of the perovskite quantum dots themselves, thereby providing them with reliable protection while maintaining their optical properties, ensuring the stable performance of quantum dots in subsequent preparation processes, and making them suitable for demanding optical application scenarios.

[0022] The polymer substrates in S2 include polyethylene, polypropylene, and polyethylene terephthalate. The polymer substrates are formed into a porous structure through the resin base foaming technology, and perovskite quantum dots are introduced. The perovskite luminescent masterbatch is prepared through a single screw extruder.

[0023] Specifically, the polymer substrate forms a porous structure through the foaming of the resin base material, providing a uniformly dispersed carrier for the perovskite quantum dots, enhancing the bonding force between the quantum dots and the substrate, and introducing the quantum dots into the porous structure through a single screw extruder to prepare the perovskite masterbatch, thereby achieving efficient dispersion and stable encapsulation of the quantum dots, thereby improving the luminescence uniformity and stability of the masterbatch, while simplifying the preparation process, reducing costs, and ensuring that the final optical composite film material has excellent optical properties, which is suitable for large-scale production of optical composite film materials.

[0024] The added concentration of the perovskite quantum dot material in S2 is 1% to 10% of the weight of the luminescent masterbatch.

[0025] Specifically, controlling the added concentration of perovskite quantum dot material at 1% to 10% of the weight of the luminescent masterbatch can flexibly adjust the luminous intensity and optical properties of quantum dots to meet the needs of different application scenarios. Low concentration (1% to 3%) is suitable for high transmittance and low brightness applications, and is suitable for mid-to-high-end LCD TVs; medium concentration (3% to 6%) balances luminous intensity and processing performance, and is suitable for high-end LCD TVs and mini-LED light conversion; high concentration (6% to 10%) is used for high-brightness display or high-temperature devices, providing high color saturation and luminous efficiency, and is suitable for commercial displays, flat panels, and car-mounted display Micro-LED light conversion. By adjusting the concentration of quantum dots, the optical properties can be precisely controlled, thereby improving the applicability and functionality of optical composite film materials.

[0026] The light diffusion substrate in S3 includes polymethyl methacrylate, polycarbonate and cycloolefin copolymer, and the weight ratio of the luminescent masterbatch to the light diffusion substrate is 1:99 to 20:80.

[0027] Specifically, polymethyl methacrylate, polycarbonate and cycloolefin copolymer are selected as light diffusion substrates with good optical and mechanical properties. At the same time, the luminescent masterbatch and the light diffusion substrate are co-extruded to ensure that the light diffusion substrate plays its stable matrix role and realizes the uniform diffusion of light, and the perovskite quantum dots in the luminescent masterbatch can effectively participate in the conversion and regulation of light, so that the light diffusion plate obtains excellent and balanced optical and mechanical properties, laying a solid foundation for the subsequent preparation of high-performance optical composite film materials.

[0028] S4 specifically includes the following steps: S101, placing the light diffusion plate into an ultrasonic cleaning machine for cleaning to remove tiny particles and impurities; S102, placing the cleaned light diffuser plate into a plasma treatment device to cause a chemical reaction on the surface of the light diffuser plate to form active sites; S103, coating a layer of tackifier on the surface of the light diffuser plate.

[0029] Specifically, S101 utilizes the cavitation effect generated when ultrasonic waves propagate in liquid. The high-frequency vibration of ultrasonic waves causes countless tiny bubbles to form inside the liquid and generates a strong impact force, which can effectively peel off and remove tiny particles and impurities attached to the surface of the light diffuser, such as dust, processing debris, and residual chemicals, etc., thereby improving the reliability and stability of subsequent processes and ensuring that the functional film and the light diffuser can be closely combined, thereby ensuring the overall performance of the optical composite film material; The plasma in S102 is rich in high-energy particles, such as electrons, ions and free radicals. These high-energy particles interact with the surface of the light diffuser plate, break the chemical bonds of the molecules on the surface of the light diffuser plate, form new active groups, and form a large number of active sites on the surface of the light diffuser plate, thereby enhancing the chemical activity and surface energy of the surface of the light diffuser plate, making it easier to chemically react and physically adsorb with the subsequent coating of the tackifier and functional film; In S103, a layer of thickener is coated on the surface of the light diffuser plate. The thickener molecules have a special chemical structure. One end of the thickener can chemically react with the active sites formed on the surface of the light diffuser plate after plasma treatment to form a strong chemical bond, while the other end can have an affinity with the functional film material to be compounded later, and is tightly combined by physical winding or chemical bonding to meet the requirements of film material reliability in various practical application scenarios.

[0030] The functional films in S5 include anti-reflection film, anti-scratch film and brightness enhancement film, and the thickness of the functional films is 0.1μm-10μm.

[0031] Specifically, the functional films include anti-reflective films, anti-scratch films and brightening films. Controlling their thickness can ensure that the functional films can exert their respective characteristics without affecting the flexibility and overall performance of the film due to being too thick, or failing to achieve the expected function due to being too thin, thereby ensuring that the optical composite film achieves a good balance between optical performance and durability.

[0032] In S6, the light diffuser plate and the functional film are integrated into a multifunctional film layer by a heat press.

[0033] Specifically, the light diffuser plate and the functional film are integrated into a multifunctional film layer with the help of a heat press. When the heat press is working, it provides ideal conditions for the fusion of the light diffuser plate and the functional film, achieves a close combination at the physical level, and forms a stable composite structure, which greatly improves the comprehensive performance of the optical composite film material, meets the stringent requirements on the optical, mechanical and other performances of the film material in different scenarios, and lays the foundation for its wide application in display, lighting and other fields.

[0034] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. An application of a perovskite quantum dot material to an optical composite film material, characterized in that: The following steps are involved: S1. Quantum dot encapsulation: First, the surface of the perovskite quantum dots is passivated with a halide matrix, and then the perovskite is isolated from the external water and oxygen with a solid inorganic material to obtain the perovskite quantum dot material; S2, preparing luminescent masterbatch: preparing luminescent masterbatch by melt blending perovskite quantum dot material and polymer substrate; S3, light diffusion plate extrusion: preparing a light diffusion plate by co-extrusion of luminescent masterbatch, light diffusion substrate and titanium dioxide, wherein the luminescent masterbatch is uniformly dispersed in the light diffusion substrate; S4, film material pretreatment: cleaning and activation of the light diffuser surface; S5. Functional film preparation: co-extruding the functional film material and the perovskite quantum dot material to prepare a functional film containing the perovskite quantum dot material; S6. Assembling optical composite film materials: The treated light diffusion plate and the functional film are assembled into optical composite film materials through a hot pressing process.

2. The application of a perovskite quantum dot material to an optical composite film material according to claim 1, characterized in that: The solid inorganic material in S1 includes silicon dioxide, silicon nitride and aluminum oxide.

3. The application of a perovskite quantum dot material to an optical composite film material according to claim 1, characterized in that: The polymer substrate in S2 includes polyethylene, polypropylene, and polyethylene terephthalate. The polymer substrate is formed into a porous structure through the resin base material foaming technology, and perovskite quantum dots are introduced to prepare perovskite luminescent masterbatch through a single screw extruder.

4. The application of a perovskite quantum dot material to an optical composite film material according to claim 1, characterized in that: The added concentration of the perovskite quantum dot material in S2 is 1% to 10% of the weight of the luminescent masterbatch.

5. The application of a perovskite quantum dot material to an optical composite film material according to claim 1, characterized in that: The light diffusion substrate in S3 includes polymethyl methacrylate, polycarbonate and cycloolefin copolymer, and the weight ratio of the luminescent masterbatch to the light diffusion substrate is 1:99 to 20:

80.

6. The application of a perovskite quantum dot material to an optical composite film material according to claim 1, characterized in that: The S4 specifically comprises the following steps: S101, placing the light diffusion plate into an ultrasonic cleaning machine for cleaning to remove tiny particles and impurities; S102, placing the cleaned light diffuser plate into a plasma treatment device to cause a chemical reaction on the surface of the light diffuser plate to form active sites; S103, coating a layer of tackifier on the surface of the light diffuser plate.

7. The application of a perovskite quantum dot material to an optical composite film material according to claim 1, characterized in that: The functional films in S5 include an anti-reflection film, an anti-scratch film and a brightness enhancement film, and the thickness of the functional films is 0.1 μm-10 μm.

8. The application of a perovskite quantum dot material to an optical composite film material according to claim 1, characterized in that: In the S6, the light diffusion plate and the functional film are integrated into a multifunctional film layer by a heat press.

Citation Information

Patent Citations

  • Light diffusion film and backlight device comprising same

    CN102753999A

  • Perovskite quantum dot membrane, quantum dot diffusion composite membrane and preparation method of quantum dot diffusion composite membrane

    CN107955199A

  • Quantum dot composition, quantum dot polymer composite, and layered structures and electronic devices including the same

    CN109749733A

  • Quantum dot optical function board, preparation method thereof and backlight module

    CN111763346A

  • Halide-coated halogen perovskite quantum dots and preparation method thereof

    CN112680215A

Cited By

  • Perovskite quantum material printing process and application thereof

    CN120133122A